Chloroquine mitigates long-term effects of in vitro culture in mouse embryos - Sato, Kaname; Koide, Itsuki; Bari, Md Wasim; Kishigami, Satoshi (Frontiers in Cell and Developmental Biology, 2025)
BackgroundIn vitro culture of preimplantation embryos may increase the risk of long-term effects, such as obesity and metabolic diseases later in life in the offspring. While the long-term consequences of low-protein diets during early development have been reported in the context of DOHaD (Developmental Origins of Health and Disease) theory, the relationship between nutrient supply via autophagy during preimplantation development and these long-term effects remains unclear. In this study, we aimed to determine whether autophagy activity during in vitro culture of mouse embryos contributes to long-term effects, using chloroquine (CQ), a known autophagy inhibitor. Preimplantation embryos were cultured in vitro in the presence of CQ. The purpose was to investigate the long-term consequences of nutrient deprivation during preimplantation development under conditions of autophagy inhibition.MethodsTwo-cell stage embryos were obtained by mating ICR female mice with ICR male mice, followed by oviduct flushing. The recovered embryos were cultured in vitro in CQ-supplemented medium. At the blastocyst stage, cultured embryos were immunostained with anti-Nanog and Cdx2 antibodies to assess blastocyst quality. Offspring derived from CQ-treated embryos were obtained by transferring the cultured embryos to pseudopregnant ICR females. At 8 weeks or later of age, offspring were examined using a glucose tolerance test.ResultsWe found that low concentration CQ significantly reduced developmental rate and total cell count in a CQ concentration-dependent manner (control: 67 ± 2.5 vs. 48 ± 2.3 with 1.0 µM CQ vs. 37 ± 2.9 with 2.0 µM CQ), as well as the numbers of trophectoderm (TE) and inner cell mass (ICM) cells. These results suggest that low concentration CQ treatment may suppress cell proliferation likely by inhibiting nutrient supply via autophagy. Notably, after implantation, the 2.0 µM CQ-treated group exhibited increased pups rate and reduced body weight comparable to the naturally mated group, and glucose tolerance similar to that of the naturally mated group, in contrasted to the untreated group.DiscussionThese findings suggest that inhibiting autophagy during preimplantation development may mitigate the long-term effects of in vitro culture and support normal postnatal growth and metabolism. Thus, autophagy activity in early development may be a key cellular process underlying long term effects observed at later stages.